Comparative Analysis of Nucleic Acid-Binding Polymers as Potential Anti-Inflammatory Nanocarriers - Divya Bhansali; Tolulope Akinade; Tianyu Li; Yiling Zhong; Feng Liu; Hanyao Huang; Zhaoxu Tu; Elsie A. Devey; Yuefei Zhu; Dane D. Jensen; Kam W. Leong (MDPI AG, 2023)
Conventionally, nanocarriers are used to regulate the controlled release of therapeutic payloads. Increasingly, they can also be designed to have an intrinsic therapeutic effect. For example, a positively charged nanocarrier can bind damage-associated molecular patterns, inhibiting toll-like receptor (TLR) pathway activation and thus modulating inflammation. These nucleic acid-binding nanomaterials (NABNs), which scavenge pro-inflammatory stimuli, exist in diverse forms, ranging from soluble polymers to nanoparticles and 2D nanosheets. Unlike conventional drugs that primarily address inflammation symptoms, these NABPs target the upstream inflammation initiation pathway by removing the agonists responsible for inflammation. Many NABNs have demonstrated effectiveness in murine models of inflammatory diseases. However, these scavengers have not been systematically studied and compared within a single setting. Herein, we screen a subset of the most potent NABNs to define their relative efficiency in scavenging cell-free nucleic acids and inhibiting various TLR pathways. This study helps interpret existing in vivo results and provides insights into the future design of anti-inflammatory nanocarriers.